Digitalization of student activity approval: a Microsoft 365 - powered solution for cost-effective & sustainable campus operation - Hashim, Mohd Sharif; Mohd Zulkifly, Mohd Zahid Ridzuan; Abdul Razak, Mohd Sufie; Abdullah, Hasanul Basri; Zabri, Jefri Khairil; Zubir, Nazira (CFS, IIUM, 2024)
The "Digitalization of Student Activity Approval" represents a groundbreaking advancement in academic administrative processes, developed using Microsoft Form and Microsoft Flow within the Microsoft 365 suite. This innovative system, provided for free by the Ministry of Education to all universities, is designed to significantly reduce the costs associated with system development while simultaneously contributing to the institution's commitment to sustainability through the reduction of paper usage. The main objective of the project is to implement a costeffective, sustainable, and efficient solution, aligning with the ministry's vision for a technologically advanced, environmentally conscious, and financially responsible educational ecosystem. In terms of practicality and sustainability, the system aligns with environmental sustainability goals by significantly reducing the reliance on paper. The system utilizes Microsoft Automate as the project's methodology. Using Artificial Intelligence, the system enhances data extraction from submitted proposals for efficient processing. Upon submission of the proposals, the system automatically identifies and notifies the next approvers in the workflow. Meanwhile, students receive real-time updates on the status of their proposals, whether they are approved, rejected, or in progress, ensuring transparency and accountability throughout the approval process. The creation and dissemination of survey questions tailored to 50 respondents: including students, advisors, administrators, and support staff. The results indicate that 80% of users found the e-proposal system easy to use, while 20% found it difficult. Additionally, 81% of users found the system to be time-efficient, 95% reported that it integrated seamlessly with existing workflows, 86% expressed general satisfaction with the system, and 85% would recommend it to others. Thus, the digitization of the student program approval system offers several advantages. It enhances efficiency and reduces the time-consuming process of manual paperwork. By automating the approval process, educational institutions can significantly save time and resources. Keywords: Digitilization, Microsoft 365 Integration, Cost-Effective Development, Green Campus Initiative, Streamlined Proposal Workflow,